Role of Social Media in Enhancing Education and Communication in India: Benefits and Challenges - Manoj Kumar; Chandra Shekhar Prajapati; Lalla Ram; Shivendra Pratap Singh; Monu Kumar; Suneel Kumar (Archives of Current Research International, 2025)
Social media are interactive media platforms that facilitate the creation and sharing of material via online networks and communities. This content might include ideas, information, expressions of many types, and hobbies. Platforms of social media such as social networks, blogs, microblogs, wikis, social bookmarking, media sharing, and RSS are available to help people get information around the globe. India is the world’s most populated country, with 1.42 billion people as of right now with its economy increasing at one of the quickest rates on the entire world. Indians use social media for 2.36 hours a day on average, and in 2023 there will be 467 million more social media users in the nation thanks to common internet access. It is truly remarkable to learn that 692 million Indians use the internet nowadays, and social media has emerged as a major factor in Indians’ everyday internet usage. The popular social media platforms YouTube, Facebook, Twitter, and LinkedIn are used in the educational sector. These days, social media plays a big role in the lives of all students. Students can also take advantage of a wide range of courses that are provided by educational institutions all around the world to increase their knowledge and skills. Students can use social media platforms to learn on their own as well. Social media poses a multitude of challenges and drawbacks, such as the possibility of addiction and distraction for educators and learners alike. Access to the internet, gadgets, and digital literacy are necessary for using social media. However, not all Indian students and teachers have not equal access to these resources. Additionally, it leads to moral conundrums like privacy, plagiarism, or bias problems.